A Multi-Targeting Approach to Fight SARS-CoV-2 Attachment - Pirone, Luciano; Del Gatto, Annarita; Di Gaetano, Sonia; Saviano, Michele; Capasso, Domenica; Zaccaro, Laura; Pedone, Emilia (Frontiers in Molecular Biosciences, 2020)
The public health has declared an international state of emergency due to the spread of a new coronavirus (SARS-CoV-2) representing a real pandemic threat so that to find potential therapeutic agents is a dire need. To this aim, the SARS-CoV-2 spike (S) glycoprotein represents a crucial target for vaccines, therapeutic antibodies, and diagnostics. Since virus binding to ACE-2 alone could not be sufficient to justify such severe infection, in order to facilitate medical countermeasure development and to search for new targets, two further regions of S protein have been taken into consideration here. One is represented by the recently identified ganglioside binding site, exactly localised in our study in the galectin-like domain, and the other one by the putative integrin binding sites contained in the RBD. We propose that a cooperating therapy using inhibitors against multiple targets altogether i.e. ACE2, integrins and sugars could be definitely more effective.